Nazism 1919-1945. (Liverpool University Press, 2014)
This is a new edition of Volume Three of the four volume collection of documents on Nazism 1919-1945, with substantial revisions to three chapters and the inclusion of many new documents, an index and a revised bibliography. The volume contains the most systematic documentation available in English of the Nazi programmes of racial and eugenic extermination, including a case study of the occupation of Poland.